Analisa Trajectory Directional Drilling Pada Sumur Berarah MST-01 - Edy Soesanto; Citra Wahyuningrum; Assyeh Annassrul M (Jurnal Bhara Petro Energi, 2024)
Directional Drilling is a drilling method that is used if there are obstacles so that the well cannot be drilled vertically. The first step in carrying out directional drilling requires planning a trajectory as a guide or reference when carrying out directional drilling. In this report, trajectory analysis was carried out to determine the parameter values used as a reference for the MST-01 well, where the results obtained from trajectory analysis on the MST-01 well were KOP 200 ftMD with a maximum inclination of 50.01°, horizontal drilling direction, namely N60 .2E, EOB length of 1667 ftMD with a total path length of 3212.19 ftMD. The trajectory model for the MST-01 well is Build and Hold with a radius of 1909.86 feet. By comparing the results of manual analysis and software, it can be concluded that there is no significant difference between the two.